Immune Exhaustion of T Cells in Alveolar Echinococcosis Patients and Its Reversal by Blocking Checkpoint Receptor TIGIT in a Murine Model. Issue 4 (24th January 2020) - Zhang, Chuanshan; Lin, Renyong; Li, Zhide; Yang, Shuting; Bi, Xiaojuan; Wang, Hui; Aini, Abudusalamu; Zhang, Ning; Abulizi, Abuduaini; Sun, Cheng; Li, Liang; Zhao, Zhibin; et al.
Abstract : Background and Aims: The cestode Echinococcus multilocularis infection, a serious health problem worldwide, causes alveolar echinococcosis (AE), a tumor‐like disease predominantly located in the liver and able to spread to any organs. Until now, there have been few studies that explore how T‐cell exhaustion contributes to the parasite's escape from immune attack and how it might be reversed. Approach and Results: In this study, we found that liver T‐cell immunoreceptor with immunoglobulin and immunoreceptor tyrosine‐based inhibitory motif domain (TIGIT) expression was significantly enhanced and positively correlated with lesion activity in AE patients. High TIGIT expression in both liver‐infiltrating and blood T cells was associated with their functional exhaustion, and its ligand CD155 was highly expressed by hepatocytes surrounding the infiltrating lymphocytes. In co‐culture experiments using human blood T cells and hepatic cell line HL‐7702, CD155 induced functional impairment of TIGIT + T cells, and in vitro blockade with TIGIT antibody restored the function of AE patients' T cells. Similar TIGIT‐related functional exhaustion of hepatic T cells and an abundant CD155 expression on hepatocytes were observed in E. multilocularis –infected mice. Importantly, in vivo blocking TIGIT prevented T‐cell exhaustion and inhibited disease progression in E. multilocularis– infected mice. Mechanistically, CD4 + T cells were totally and CD8 + T cells partially required for anti‐TIGIT–induced regression of parasite growth in mice. Conclusions: This study demonstrates that E. multilocularis can induce T‐cell exhaustion through inhibitory receptor TIGIT, and that blocking this checkpoint may reverse the functional impairment of T cells and represent a possible approach to immunotherapy against AE.